2018
DOI: 10.1038/s41409-018-0149-x
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal development and sexual functioning in young women after stem cell transplantation, chemotherapy, and/or radiotherapy for childhood hematological diseases

Abstract: To study vaginal development and sexual functioning in young women after childhood hemopoietic stem cell transplantation (HSCT) and radio/chemotherapy. Observational case-control study on 30 young sexually active women survived after HSCT and/or radio/chemotherapy for childhood malignancies or hematologic diseases and 48 controls matched for age. Female Sexual Function Index was lower (median 24.05, IQR = 17.30-28.30 vs. 29.00, IQR = 25.30-31.40, p = 0.001), Female Sexual Distress Scale higher (median 16.00, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…[7] The literature review resulted in one category C article meeting inclusion criteria for the present review (Table 1). [91] In the aforementioned study, young adult female CCS who had received TBI (dose not reported) before hematopoietic stem cell transplantation during childhood, reported lower Female Sexual Function Index score, indicating issues in sexual functioning, and showed a trend towards shorter vaginal length compared to survivors in the chemotherapy and RT (chest or abdominopelvic, dose not reported) group. [91] The aforementioned study provides insufficient information to recommend specific dose constraints for the vaginal wall.…”
Section: Vaginal Toxicity and Sexual Functioningmentioning
confidence: 89%
“…[7] The literature review resulted in one category C article meeting inclusion criteria for the present review (Table 1). [91] In the aforementioned study, young adult female CCS who had received TBI (dose not reported) before hematopoietic stem cell transplantation during childhood, reported lower Female Sexual Function Index score, indicating issues in sexual functioning, and showed a trend towards shorter vaginal length compared to survivors in the chemotherapy and RT (chest or abdominopelvic, dose not reported) group. [91] The aforementioned study provides insufficient information to recommend specific dose constraints for the vaginal wall.…”
Section: Vaginal Toxicity and Sexual Functioningmentioning
confidence: 89%
“…Subsequent treatment included no suppressible gonadotropins, with sequential estradiol and progestin (estradiol hemihydrate 2 mg during 12 days; norethisterone acetate 1 mg during 10 days plus estradiol hemihydrate 2 mg and finally only estradiol hemihydrate 1 mg during 6 days). The median age at disease onset was 10.5 years (0-18), the median age at treatment onset was 16 years (11)(12)(13)(14)(15)(16)(17)(18), and the median duration of treatment in group A patients was 12 years (4-36) ( Tables 1 and 2). Group B included 69 patients.…”
Section: Methodsmentioning
confidence: 99%
“…The median age at diagnosis was 44 years (41-51) and the median age at treatment onset was 46 years (42-59). They underwent treatment during a median period of 10 years (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). All data concerning this cohort is explained in Tables 1 and 2.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations